"\\frac{d^2 y}{dx^2} + 4 \\frac{dy}{dx} + 13y = 0; y(0)=1, y'(0)=4"
The given equation can be written as
"(D^2 + 4D + 13)y = 0; y(0)=1, y'(0)=4."
The auxiliary equation is,
"m^2 + 4m + 13 = 0"
Solving for m,
"m = \\frac{-4 \\pm \\sqrt{16 - 4*13}}{2}\\\\ \n~~~~~=\\frac{-4 \\pm \\sqrt{-36}}{2} \\\\~~~~~ = -2 \\pm 3i.\\\\"
The solution is,
"y(x) = e^{-2x}(A \\cos 3x + B \\sin 3x),"
where A and B are constants.
To find A and B, we use the given initial conditions
y(0)=1, y'(0)=4.
Now,
"y'(x) = e^{-2x}(-3A \\sin 3x + 3B \\cos 3x)\\\\~~~~~~~~~~~~~~~~~ - 2e^-2x(A \\cos 3x + B \\sin 3x)\\\\\n~~~~~= e^{-2x}(-3A \\sin 3x + 3B \\cos 3x) - 2y(x)."
Using the condition
y(0) = 1, in y(x) we get A = 1.
Using the condition
y(0) = 1, y'(0) = 4 and A = 1 in y'(x), we get
y'(0) = (0 + 3B) - 2y(0)
4 = 3B - 2
B = 2.
Thus, the solution is
"y(x) = e^{-2x}(\\cos 3x + 2 \\sin 3x)."
Comments
Leave a comment